Putative regulatory functions of SNPs associated with bronchial asthma, arterial hypertension and their comorbid phenotype - I. A. Goncharova; E. Yu. Bragina; I. Zh. Zhalsanova; M. B. Freidin; M. S. Nazarenko (Вавиловский журнал генетики и селекции)
Linkage disequilibrium (LD) of single nucleotide polymorphisms (SNPs) of TLR4/AL160272.2 (rs1927914, rs1928298, rs7038716, rs7026297, rs7025144) was estimated in the Slavs of West Siberia. We further investigated an association of SNPs in TLR4/AL160272.2 (rs1927914, rs7038716, rs7025144), SERPINA1 (rs1980616), ATXN2/BRAP (rs11065987), IL2RB (rs2284033), NT5C2 (rs11191582), CARD8 (rs11669386), ANG/RNASE4 (rs1010461), and ABTB2/ САТ (rs2022318) genes with bronchial asthma (BA), arterial hypertension (AH) and their comorbidity. Then, the disease-associated SNPs were annotated in silico in relation to their potential regulatory functions. Strong LD was detected between rs1928298 and rs1927914, as well as rs7026297 and rs7038716 in the Slavs of West Siberia. It was found that the rs1927914 G allele of the TLR4 gene and the rs1980616 C allele of the SERPINA1 gene are associated with the predisposition to BA. These SNPs can affect binding affinity of transcription factors of the Pou and Klf4 families, as well as the expression levels of the TLR4 and SERPINA1 genes. The rs11065987 allele A of the ATXN2/BRAP genes, the rs11669386 A allele of the CARD8 gene, the rs2284033 allele G of the IL2RB gene, and the rs11191582 allele G of the NT5C2 gene were associated with the risk of AH. These variants can alter binding affinity of the Hoxa9, Irf, RORalpha1 and HMG-IY transcription factors, as well as the expression levels of the ALDH2, CARD8, NT5C2, ARL3, and SFXN2 genes in blood cells/vessels/heart, respectively. The risk of developing a comorbid phenotype of AD and AH is associated with the A allele of rs7038716 and the T allele of rs7025144 of the TLR4/AL160272.2 genes, the A allele of rs1010461 of the ANG gene and the C allele of rs2022318 of the ABTB2/CAT genes. Variants rs7038716 and rs7025144 can change the expression levels of the TLR4 gene in blood cells, while rs1010461 and rs2022318 influence the expression levels of the ANG and RNASE4 genes as well as the CAT and ABTB2 genes in blood cells, lungs/vessels/heart.